Genomic insights into the genetic diversity and genetic basis of body height in endangered Chinese Ningqiang ponies - Jiale Han; Hanrui Shao; Minhao Sun; Feng Gao; Qiaoyan Hu; Ge Yang; Halima Jafari; Na Li; Ruihua Dang (BMC Genomics)
Abstract Background Genetic diversity in livestock and poultry is critical for adapting production systems to future challenges. However, inadequate management practices, particularly in developing countries, have led to the extinction or near extinction of several species. Understanding the genetic composition and historical background of local breeds is essential for their effective conservation and sustainable use. This study compared the genomes of 30 newly sequenced Ningqiang ponies with those of 56 other ponies and 104 horses to investigate genetic diversity, genetic differentiation, and the genetic basis of body height differences. Result Population structure and genetic diversity analyses revealed that Ningqiang ponies belong to southwestern Chinese ponies. They exhibit a moderate level of inbreeding compared to other pony and horse breeds. Mitochondrial DNA analysis indicated that Ningqiang and Debao ponies share the dominant haplogroups A and C, suggesting a likely common maternal origin. Our study identified low genetic differentiation and detectable gene flow between Ningqiang ponies and Datong horses. The study also indicated the effective population size of Ningqiang ponies showed a downward trend. These findings potentially reflect the historical formation of Ningqiang ponies and population size changes. A selection signal scan (CLR and θπ) within Ningqiang ponies detected several key genes associated with bone development (ANKRD11, OSGIN2, JUNB, and RPL13) and immune response (RIPK2). The combination of genome-wide association analysis and selective signature analysis (F ST) revealed significant single nucleotide polymorphisms and selective genes associated with body height, with the most prominent finding being the TBX3 gene on equine chromosome (ECA) 8. Additionally, TBX5, ASAP1, CDK12, CA10, and CSMD1 were identified as important candidate genes for body height differences between ponies and horses. Conclusion The results of this study elucidate the genetic diversity, genetic differentiation, and effective population size of Ningqiang ponies compared to other ponies and horses, further deepen the understanding of their small stature, and provide valuable insights into the conservation and breeding of local horse breeds in China.